Učinek računalniškega kognitivnega treninga prostorske navigacije na kognitivne sposobnosti pri nadarjenih učencih - Slatenšek, Barbara (Psihološka obzorja (Ljubljana), 2021)
Spatial navigation is a complex cognitive skill and one that is necessary for daily activities in any environment. It depends on a wide spectrum of cognitive abilities. The purpose of the study was to examine whether cognitive training of spatial navigation with gifted students can improve their capacity of short-term memory, working memory, visuospatial memory, and verbal memory, along with increasing the speed of processing and executive functions. Twenty-eight fifth- and sixth-grade pupils who had been identifi ed as gifted and had scored above average on Standard Progressive Matrices (SPM) intelligence test took part in the study. Thirteen gifted students were included in the experimental group in which they trained virtual maze navigation in 8 sessions each lasting 45 minutes per week. The rest of the gifted students (n = 15) were assigned to the passive control group. Results showed that cognitive training was eff ective since the students in the experimental group as compared with the students from the control group achieved signifi cantly better results after cognitive training on the tests measuring processing speed and immediate recall of visuospatial information. The improved performance of these cognitive abilities demonstrates that the cognitive training is effective with gifted students. Thus, the application of cognitive training seems sensible with gifted students even though they already possess advanced cognitive capacities.
Keywords: cognitive abilities; cognitive training; gifted pupils; kognitivne sposobnosti; kognitivni trening; nadarjeni učenci; prostorska navigacija; spatial navigation; virtual maze; virtualni labirint